Peripherally Inserted Central Venous Catheters in Critically Ill Premature Neonates. Issue 4 (October 2013) - Ozkiraz, Servet; Gokmen, Zeynel; Ince, Deniz Anuk; Akcan, Abdullah Baris; Kilicdag, Hasan; Ozel, Deniz; Ecevit, Ayse
Purpose: To evaluate the safety of peripherally inserted central venous catheters (PICCs) and their complications in critically ill premature neonates. Methods: A retrospective collection of data of infants with very low birth weight (VLBW) who underwent PICC placement over a 2-year period. Gestational age, birth weight (BW), sex, site of catheter placement, reason for catheter removal, duration of the catheter use, proven sepsis, type of the reported organism and the rate of complications were collected. The infants were classified into two groups according to BWs: Group 1–-VLBW infants (BW between 1, 000 and 1, 500 g) and Group 2–-BW <1, 000 g (extremely low birth weight, ELBW group). Results: During the study period, 90 VLBW infants were admitted to the neonatal intensive care unit. PICCs were attempted in 71 patients. A PICC was successfully inserted into 62 patients (87.3%). Totally, 68 PICCs were inserted into 62 infants. PICCs placed in either the upper or the lower extremity have no differences in complication rates. The median time of catheter insertion was 10 (1-22) days for Group 1 and 16 (1-47) days for Group 2 (p=0.001). The median duration of PICCs was 9 (2-18) and 12.0 (3-30) days, respectively (p=0.012). There were no significant differences between groups for the reasons for removal (p=0.859). Conclusions: PICCs are convenient for the administration of long course antibiotics and parenteral nutrition for both VLBW and ELBW infants. The risk of catheter complications did not increase in ELBW infants. Although the technique of insertion is easy and using PICCs has many benefits, serious and fatal complications may occur in premature neonates in critical states.